KAJIAN LEKSIKON ATAS TERJEMAH AL-QUR’AN BERSAJAK SHAWKAT M. TOORAWA: Metode, Lexical Echo, dan Hapax - Nur Fiatin Hafidh; Fairuzah (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2023)
Abstract Shawkat M. Toorawa is a contemporary figure who wants to show the unity of Al-Qur’an by presenting its rhyming translation. According to him, the translator ideally should not only focus on how to copy the content to the diverse languages, but should also maintain the feel of the original text. Because of his translation orientation prioritizes readers understanding – not just copying the text-, he is very detailed and careful in looking for appropriate equivalents of the translated words, including lexical echo and hapax in the Al-Qur’an. Using descriptive analysis method and linguistic approach, the author means to examine Shawkat M. Toorawa’s translation method, as well as his perspective about lexical echoes and hapaxes in the Al-Qur’an. This research reveals three findings. One, the Toorawa’s translation uses a micro-structure approach, it caused the study of micro-structure of the text can produce a macro understanding of the text itself. Two, lexical echo in Al-Qur’an has function to maintain the narrative of the text because it ties the verse that comes later with the previous verse. Three, Toorawa maintains the unique structure of hapax by creating meaning that is appropriate as well as not popularly used in the meaning of other words. Keywords: translation of Al-Qur’an, Shawkat M. Toorawa, rhyme, lexical echo, hapax